Efektivitas Continuum of Care Terhadap Kemampuan Ibu Dalam Perawatan Bayi di Kota Makassar - Siti Mukarramah; Afriani Afriani; Amanda Damayanti; Marhaeni Marhaeni; Wirawati Amin (Direktorat Politeknik Kesehatan Makassar, 2025)
Every child has the right to live, grow, develop, and be protected. To that end, comprehensive, integrated, and sustainable child health efforts must be carried out from the fetal stage to the age of 18 to ensure the survival and quality of life of children through a reduction in mortality rates, improved nutrition, and the fulfillment of minimum service standards for infants. This study aims to analyze the relationship between the implementation of Continuum of Care (COC) and mothers' ability to care for infants, focusing on health aspects and caregiving skills, to improve infant care quality and reduce complications. The method used is quantitative with an observational analytical approach and a case-control design. The study sample consisted of 76 mothers, with 38 mothers receiving COC services and 38 mothers not receiving such services. Data were analyzed using the chi-square test and Odds Ratio (OR) calculations. The results showed that mothers who received COC services had better infant care skills compared to those who did not. Among the 38 mothers who received COC, 89.4% were able to care for their infants well, while only 34.2% of mothers who did not receive COC were able to care for their infants. The p-value of 0.000 indicates that this difference is statistically significant. The Odds Ratio shows that mothers who did not receive COC services were 16 times more likely to be unable to care for their infants compared to those who received COC (OR = 16.346). This study concludes that the implementation of the COC program significantly improves mothers' ability to care for their babies WITH A p-VALUE OF 0.000. Therefore, it is recommended that the COC program be widely implemented to improve the quality of infant care and the health of mothers and children. Keywords: Continuum of Care; Maternal Ability; Infant Care; Maternal Health; Child Health